Dampak Konversi Lahan Pertanian Menjadi Kawasan Perumahan terhadap Pendapatan Petani di Kecamatan Maritengngae Kabupaten Sidenreng Rappang - Fitria, Fitria; Iranita Haryono; Astrini Padapi (LP3M Universitas Putra Bangsa, 2025)
This research will provide information about how the conversion of agricultural land into residential areas affects farmers' income. Understanding their impacts can help in developing strategies to protect or improve the welfare of affected farmers. The aim of the research is to determine the impact on farmers' income after the conversion of agricultural land into a residential area in the Maritengngae sub-district, Sidrap Regency. The research was conducted in 2024 between January and March. Secondary data was collected from various online sources, statistical agencies and scientific publications, primary data was obtained through direct interviews with farmers using questionnaires. The sampling strategy uses saturated samples and probability sampling methods. Farmers in Maritengngae District, Sidenreng Rappang Regency who carried out land conversion were used as research samples. Land conversion has an impact on income. Farmers experience a decrease in income after land conversion due to loss of agricultural land. Apart from that, the impact also occurs in the form of reducing the area of ​​agricultural land and affecting the balance of the agricultural land ecosystem.